Analisis Standar Nasional Indonesia Bidang Perpustakaan dan Bidang Dokumentasi di Indonesia - Rochani Rahayu; Noer'aida Noer'aida (Perpustakaan Universitas Riau, 2023)
The research aims to find out; 1) Number of SNIs in the library and documentation sector in Indonesia; 2) Number of valid and invalid SNIs; 3) Number of available and unavailable full text of SNI; 4). SNI made by adoption and not adoption. The keyword